A 10-year bibliometric analysis in the field of osteosarcoma treatment from 2014 to 2023 - Yiguo Shen; Xiaobo Shao; Jiansong Chen; Xin Tang (Discover Oncology)
Abstract Objective This paper aims to explore the research hot spot and development trend in osteosarcoma treatment using a bibliometric method based upon Web of Science Core Collection (WoSCC) platform over the last decade. Methods The literature related to osteosarcoma and cure which were published from January 2014 to December 2023 were retrieved from the database of WoSCC and made an overall analysis for the papers published including number of articles, distribution of countries and institutions, author information, and keywords, with the CiteSpace 6.2.R5. Results A total of 3131 papers were retrieved, including 2601 articles and 530 reviews, and the number of papers published has been increasing year by year in the last decade. There were 415 countries and 10,719 research institutions participating into the study. China’s output of literature was the highest relying on its 1490 papers published, followed by The United States (548 papers). Shanghai Jiaotong university had the largest number of papers published (121 papers) and Central South University ranked second (82 papers). A total of 16,816 authors participated in the study. The number of the paper published by Massimo Serra of the Rizzoli Orthopaedics Institute was the largest (27 papers), followed by Dominique Heymann of the University of Sheffield (20 papers). The visualization analysis of keywords by CiteSpace software showed that the drug resistance, drug delivery, tumor tissue engineering and gene expression have become hotspots in the field of osteosarcoma treatment. Drug resistance significantly limits the effectiveness of current cancer treatments. Drug delivery technology not only enhances the targeting and efficacy of drugs but also helps to overcome drug resistance. The stem cells, targeted therapy, and tumor microenvironment represent the new research trends. In particular, the tumor microenvironment plays a key role in tumor development, progression, and drug resistance, and it offers numerous potential therapeutic targets. Conclusion Our investigation has identified key research foci and hotspots in osteosarcoma treatment, including drug resistance mechanisms, innovations in drug delivery technology, stem cell development, tumor microenvironment analysis, the development of novel therapies, and the clinical translation of tumor tissue engineering.